Field Trip Learning Management In The Pancasila Students Profile Strengthening Project - Rahmawati, Marlina Indra; Arifin, Imron; Supriyanto, Achmad (Proceedings Series of Educational Studies, 2024)
Field trips are learning that takes place outside the classroom, such as at tourist attractions. The material provided must adapt to the material during class learning. So by applying this method, especially at elementary school level, it will increase students' curiosity about the objects being observed, apart from that, this method also trains students' character to be responsible for things around them. This research aims to describe: (1) school preparations in implementing the field trip learning method; (2) describe the implementation of the field trip learning method for regular and inclusion students; (3) describe the differences in the application of the field trip learning method before and after the independent curriculum; (4) describe the effectiveness of implementing the field trip learning method in Project for Strengthening Pancasila Student Profiles. Keywords: management; field trip; independent curriculum; character building; Pancasila students.